Phenotypic flexibility in background-mediated color change in sticklebacks. (6th May 2020) - Tibblin, Petter; Hall, Marcus; Svensson, P Andreas; Merilä, Juha; Forsman, Anders
Abstract: Phenotypic flexibility may incur a selective advantage in changing and heterogeneous environments, and is increasingly recognized as an integral aspect of organismal adaptation. Despite the widespread occurrence and potential importance of rapid and reversible background-mediated color change for predator avoidance, knowledge gaps remain regarding its adaptive value, repeatability within individuals, phenotypic correlates, and whether its expression is context dependent. We used manipulative experiments to investigate these issues in two fish species, the three-spined stickleback ( Gasterosteus aculeatus ) and nine-spined stickleback ( Pungitius pungitius ). We sequentially exposed individuals to dark and light visual background treatments, quantified color change from video recordings, and examined associations of color change with phenotypic dimensions that can influence the outcome of predator-prey interactions. G. aculeatus expressed a greater degree of color change compared to P. pungitius . In G. aculeatus, the color change response was repeatable within individuals. Moreover, the color change response was independent of body size but affected by sex and boldness, with males and bolder individuals changing less. Infection by the parasite Schistocephalus solidus did not affect the degree of color change, but it did modulate its association with sex and boldness. G. aculeatus adjusted the expression of color change in response to predation risk, with enhanced color change expression in individuals exposed to either simulated attacks, or olfactory cues from a natural predator. These results provide novel evidence on repeatability, correlated traits, and context dependence in the color change response and highlight how a suite of factors can contribute to individual variation in phenotypic flexibility. Abstract : Many organisms change their coloration rapidly as a response to visual backgrounds to avoid detection from predators. The capacity to change coloration varies not only between species but also among individuals within species. However, the sources of individual variation in color changing behavior are poorly understood. By studying sticklebacks, we show that color changing behavior was influenced by sex, boldness, and parasite infection. Moreover, individuals also changed their color to a higher degree when at risk of predation.